Mistreatment in lockup: a study of the prisons regulations 2000 / Farah Adlin Ahmad and Mohd Redzuan Cyril Pancratius - Ahmad, Farah Adlin; Cyril Pancratius, Mohd Redzuan (2006)
The last two semesters had been dedicated to conduct a research based on the nude squat case that had sparked public uproar in 17 November 2005. The research was done with the objective to find out the sufficiency of the existing law on the treatment of the suspected person whilst in police custody. The relevancy of the application of the Standing Orders made by the Inspector General in the treatment of the suspected person was also been taken into consideration. We also wanted to investigate whether the law was made in accordance with the international principles made by the United Nations. The cases that were being highlighted by the media is our main resource of information since most of these cases that involves the abuse or the death of the suspected person whilst in police custody had not been brought to the court of law. All these issues were then looked into from the perspective of the Prisons Regulations 2000. We conducted interview session with experts that deal with the issue of abuse and death of the suspected person whilst in police custody almost in daily basis. The outcomes of these interviews were as we expected. We benefited a lot from the interviews since most of the recommendations were relevant for the purpose of this research. Among questions forwarded to the respondents are on the sufficiency of the existing laws, establishment of the Independent Police Complaints and Misconduct Commission (IPCMC) and on the J publication of the Inspector General of Police's Standing Orders. Our research is also based on the literatures written by authors specialising in this area and also materials we find online.